2021
DOI: 10.3390/lubricants9040039
|View full text |Cite
|
Sign up to set email alerts
|

Study of Jatropha curcas Linn and Olea europaea as Bio-Oil Lubricant to Physical Properties and Wear Rate

Abstract: This paper presents a study on the effect of the mixed volume fraction of Jatropha curcas Oil (JCO) and Olea europea or extra virgin olive oil (EVOO) on the physical properties of the oil, especially viscosity, density and water content. This study also presents the mechanical properties examination result, especially its effect on the wear rate of the pin on disc tribometer results on ST 41 steel specimens, using optical microscopy. The independent variables used were variations of the oil mixture: 0, 20, 40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…According to the study, a change in load shows an impact on wear rate. The findings were consistent with previous research [33]. The study suggested that inclusion of anti-wear additive in EC-CMC and PTFE will enhance their tribological properties and will be comparable to commercial shell counterpart.…”
Section: Tribo-pair Volume Wear Ratesupporting
confidence: 92%
“…According to the study, a change in load shows an impact on wear rate. The findings were consistent with previous research [33]. The study suggested that inclusion of anti-wear additive in EC-CMC and PTFE will enhance their tribological properties and will be comparable to commercial shell counterpart.…”
Section: Tribo-pair Volume Wear Ratesupporting
confidence: 92%
“…One is the lubrication film formed between friction pairs. The other is the decreased contact pressure due to the enlarged WSS [34]. The results indicated that CPSO can provide long-term effective lubrication even when the temperature is up to 350 °C.…”
Section: Tribological Performancementioning
confidence: 92%
“…Through a four-step catalytic process, bio lubricants can also be made from used cooking oil and cyclic oxygenates. Some experts have noted that viscosity is the most significant characteristic of lubricants since it controls the degree of friction between two surfaces 13,20) . Higher viscosity lubricants have lower wear rates and a higher viscosity ratio, which reduces wear 20) .…”
Section: Why Bio-lubricantmentioning
confidence: 99%